Control de la inversión operativa y su impacto en el capital de trabajo de las empresas pesqueras - Altamirano Guzmán, Maribel Elizabeth (2021)
Working capital is the difference between current assets and current liabilities, it is important because it indicates the ability of the company to cover its daily operations in the short term. Sound capital management is therefore a prerequisite for the survival of the enterprise; This research paper will examine the challenges of financial management of working capital accounts and the impact this can have on the profitability of enterprises in the fisheries sector, therefore aims to determine optimal values for the current assets and liabilities of the firms under consideration, since the greater the difference between them the less need for financing to cover short-term liabilities, therefore the financial stability of the company depends on efficient management of working capital. For those who handle inventory of goods, the control, registration and valuation of goods is one of the most difficult challenges that the accountant will have to face and resolve. Inventoryrelated account become the most important accounts, and the results of the transactions with the goods they represent will depend on the success or failure of the business objective: to make a profit. The reason for this study allows us to analyze the impact of the management of working capital on the profitability of fishing companies based on existing capital management concepts and theories........